A cuboidal [Ni4O4] cluster as a precursor for recyclable, carbon-supported nickel nanoparticle reduction catalysts. Issue 22 (19th May 2017) - Yuan, Yan-Qiu; Yuan, Feng-Ling; Li, Fei-Long; Hao, Zhi-Min; Guo, Jun; Young, David J.; Zhang, Wen-Hua; Lang, Jian-Ping
Abstract : A pyridine alkoxide ligated cuboidal [Ni4 O4 ] cluster has been selected as the precursor to synthesize carbon-hosted Ni nanoparticles for catalytic conversion of 4-nitrophenol to 4-aminophenol. Abstract : Cuboidal [Ni4 O4 ] clusters supported by a pyridine alkoxide ligand have been developed. One of these clusters was selected as a precursor for carbon-hosted Ni nanoparticles (NiNPs/C) which were efficient catalysts for the conversion of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) at room temperature.